(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Rambutan (Nephelium lappaceum L.) is a significant fruit in southeast Asia that has garnered increased interest in recent years due to its succulent and sweet nature, as well as its invigorating taste and unique look. The nutritional and functional characteristics of this product make it a widely favoured option for commercialization. This paper explores the bioactive chemicals present in the fruit, peel, and seed. The peel is known to contain antioxidants that have significant importance in several sectors, like cosmetics, pharmaceuticals, and food. The peel extracts have shown several beneficial benefits including, antibacterial, antioxidant, antidiabetic, anti-inflammatory, and antiproliferative properties. Rambutan seed also contains a lot of high-quality fat, protein, carbs, fibre, vitamins, and phenolics, and it can be used in many areas of the food, drug, and cosmetics industries. Nevertheless, more examination is required in order to comprehend the nutritional and phytochemical capabilities of the fruit, as well as the therapeutic processes included in its industrial cultivation as a functional or medicinal food item.